Revisiting Recombination Signal in the Tick-Borne Encephalitis Virus: A Simulation Approach - Bertrand, Yann J K; Johansson, Magnus; Norberg, Peter (PloS one, 2016)
The hypothesis of wide spread reticulate evolution in Tick-Borne Encephalitis virus (TBEV) has recently gained momentum with several publications describing past recombination events involving various TBEV clades. Despite a large body of work, no consensus has yet emerged on TBEV evolutionary dynamics. Understanding the occurrence and frequency of recombination in TBEV bears significant impact on epidemiology, evolution, and vaccination with live vaccines. In this study, we investigated the possibility of detecting recombination events in TBEV by simulating recombinations at several locations on the virus' phylogenetic tree and for different lengths of recombining fragments. We derived estimations of rates of true and false positive for the detection of past recombination events for seven recombination detection algorithms. Our analytical framework can be applied to any investigation dealing with the difficult task of distinguishing genuine recombination signal from background noise. Our results suggest that the problem of false positives associated with low detection P-values in TBEV, is more insidious than generally acknowledged. We reappraised the recombination signals present in the empirical data, and showed that reliable signals could only be obtained in a few cases when highly genetically divergent strains were involved, whereas false positives were common among genetically similar strains. We thus conclude that recombination among wild-type TBEV strains may occur, which has potential implications for vaccination with live vaccines, but that these events are surprisingly rare.
Keywords: viry klíšťové encefalitidy; molekulární evoluce; Viral Vaccines; rekombinace genetická; virové vakcíny; Encephalitis Viruses, Tick-Borne; fylogeneze; Phylogeny; Recombination, Genetic; Evolution, Molecular